Himne sebagai Inspirasi Konsep Redesain Gereja Baptis Efrata di Bandung - Purnomo, Agus Dody; Hapsoro, Agustinus Nur Arief; Yap, Angel Brielle; Kahagi, Chelsea Angelica (ARCHIHUMANUM, 2023)
The Efrata Baptist Church in Bandung was established in 1967 planning renovations to increase the congregation's capacity. Building renovations put more emphasis on optimizing the existing buildings. For this reason, it is necessary to redesign, among others: seating capacity, interior atmosphere, baptismal pool, and building facades. The design objective is to prepare a church design that is functional and has a narrative of Christian values. The method uses a design method with a semiotic approach. The design stage starts from data collection, data analysis stage, synthesis stage to the application of the design concept. The redesign concept was inspired by the lyrics of the Cwm Rhondda hymn. This is because music and church cannot be separated. And one genre of church music that is familiar with the Baptist church is hymns. The lyrics of the Cwm Rhondda hymn are applied through the architectural elements of the church.